PENGARUH PENGGUNAAN MEDIA EDUCAPLAY TERHADAP HASIL BELAJAR PESERTA DIDIK DALAM PEMBELAJARAN IPAS (BAB 1 TOPIK A. ADA HEWAN APA SAJA DI SEKITARMU) DI KELAS 3 SDN 4 PARAKANNYASAG - Fitri Rahmawati; Budi Hendrawan; Sunanih (STKIP Subang, 2026)
This research is motivated by the low value of science in grade 3 of SDN 4 Parakannyasag. The purpose of this study is to determine the effect of educaplay media on student learning outcomes in science learning (Chapter 1 topic A. What animals are around you) in grade 3 of SDN 4 Parakannyasag. This study uses quantitative research with experimental methods. This type of research is Pre-Experimental with One-Group Pretest Posttest design. The sampling technique in this study uses saturated sampling technique. The population of this study is all grade 3 students of SDN 4 Parakannyasag with a sample of 28 students. Data collection techniques used in this study are observation, interview, test and documentation techniques. Based on the results of the research and discussion analysis, the data in this study are normally distributed and homogeneous with a significance level of data normality of 0.09> 0.05, and a significance level of data homogeneity of 0.33> 0.05. Hypothesis testing in this study uses paired sample t-test (t-test). Based on the results of the hypothesis test, the significance value of learning outcomes was 0.00 < 0.05. So it can be concluded in this study that Ho is rejected and Ha is accepted, meaning that the educaplay media has an effect on student learning outcomes in science learning (Chapter 1 topic A. What animals are around you) in grade 3 of SDN 4 Parakannyasag.